A New Paradigm of Digital Payment Satisfaction: Empirical Evidence of Holistic Transaction Behavior among Digital Natives in Bandung City - Akbar Fadhl Ramadhan; Evan Ferdinand; Fazril Muhammad Mursyidan; Rakha Yathaqi Witsqa (International Journal Administration, Business & Organization, 2026)
This study aims to examine the individual and collective influence of ease of use, transaction speed, and system security on the satisfaction of Generation Z university students using QRIS and e-wallet payment services in Bandung City, Indonesia. A quantitative causal-explanatory research design was employed, with primary data collected from two hundred and forty-seven eligible respondents through structured online questionnaires. Instrument quality was verified through Pearson correlation validity testing, Cronbach's Alpha reliability analysis, and Principal Component Analysis via IBM SPSS Statistics. The structural model was evaluated using Partial Least Squares Structural Equation Modeling through SmartPLS 4, incorporating outer model assessment, inner model evaluation, and bootstrapping procedures. The results indicate that none of the three predictor constructs individually reached the conventional threshold of statistical significance; however, the three constructs collectively demonstrated an exceptionally high level of explanatory power over Generation Z student satisfaction. Theoretically, this study extends the Technology Acceptance Model within the context of Indonesia's national digital payment infrastructure, providing evidence that Generation Z evaluates digital payment quality through an integrated, holistic experiential process rather than discrete attribute-by-attribute assessment. Practically, the findings offer strategic recommendations for digital payment service providers, national regulators, and university administrators seeking to optimize Generation Z satisfaction within Indonesia's evolving cashless ecosystem. As a novel contribution, this study proposes holistic transaction behavior as a conceptual explanation for the co-occurrence of individually non-significant predictors and exceptional collective predictive power in PLS-SEM models applied to Generation Z digital service evaluation contexts.